Beyond clinical skills: student-reported impacts of a veterinary public health externship in rural Alaska - Meythaler-Mullins, Laurie; Lobdell, Allyce H.; Kern-Allely, Caroline; Frey, Danielle M. (Frontiers in Veterinary Science, 2025)
Preventive medicine and public health are critical components of veterinary curricula, requiring students to understand their role in the health of communities and people beyond their animal patients. However, students considering a career in public health often face gaps in the depth of this curriculum. From 2019 to 2024, students from Colorado State University (CSU) and its University of Alaska Fairbanks (UAF) partner participated in the Hub Outpost Project (HOP) externship’s community visits to Yukon-Kuskokwim Delta communities in rural Alaska. The curriculum emphasized veterinary professional concepts, surgical and clinical experience, community engagement and cultural awareness, and self- and team- mindfulness. Through repeated practice and direct exposure to providing care, students improved a variety of clinical and professional skills. Student impacts were assessed through a survey of the participating veterinary students from both institutions. Students primarily reported impacts related to gaining clinical and communication skills, the breadth of human-animal bonds, engaging directly with clients and patients, and realizations and understandings that quality medicine is possible with limited resources. These findings suggest that experiential learning not only greatly improves skills for students but also engages students in areas of veterinary medicine that need an increased workforce, such as rural medicine, while increasing their understanding of diverse community needs.